1992
DOI: 10.1177/0310057x9202000307
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Anaesthetic Tubing – a Real Hazard?

Abstract: This study aimed to find whether a patient placed on an anaesthetic machine could contaminate the tubing resulting in possible cross-infection to subsequent patients. Twenty randomly chosen anaesthetic circuits were collected after use during operations and cultured for bacteria and fungi. These were compared with ten circuits which had been washed and dried. Another ten washed circuits were attached to an anaesthetic machine and each circulated with air for four hours before similar cultures were performed. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
(2 reference statements)
0
9
0
4
Order By: Relevance
“…Microbes expelled by a patient which do pass through a breathing system filter will attach to the walls of the breathing system. Ibrahim and Perceval [26] demonstrated that air passing through breathing system tubing ‘seeded’ with microbes did not become contaminated. Nielsen and colleagues measured a mean bacterial count of 0.385 l −1 (range 0.033–1.298 l −1 ) in a 50% oxygen in nitrous oxide mixture delivered through a ‘seeded’ breathing system [27].…”
Section: Discussionmentioning
confidence: 99%
“…Microbes expelled by a patient which do pass through a breathing system filter will attach to the walls of the breathing system. Ibrahim and Perceval [26] demonstrated that air passing through breathing system tubing ‘seeded’ with microbes did not become contaminated. Nielsen and colleagues measured a mean bacterial count of 0.385 l −1 (range 0.033–1.298 l −1 ) in a 50% oxygen in nitrous oxide mixture delivered through a ‘seeded’ breathing system [27].…”
Section: Discussionmentioning
confidence: 99%
“…[3,4,5,6]. Nach Inhalationsnarkosen ohne ASF betrug die Kontaminationsrate von Narkoseschlauch-und Atemsystem 8-13% [7,8,9,10], darunter jedoch nur selten lungenpathogene Erreger [9]. Das virale Übertragungsrisiko wird als vergleichsweise gering eingeschätzt [1,2].…”
Section: Aufbereitung Des Narkosegerätsunclassified
“…After use on the patient, all breathing gas conducting parts of the anaesthetic system can therefore be contaminated with pathogens, with the greatest levels of contamination being detectable close to the patient [10], [11], [12], [13]. After inhalation anaesthesia without BSF, the contamination rate of the anaesthesia breathing system and circle system amounted to 8–13% [14], [15], [16], [17], however, showing pulmonary pathogens only rarely enter the breathing system [16]. The risk of viral transmission is considered to be comparatively low [1], [2].…”
Section: Explanation Reportmentioning
confidence: 99%